2020
DOI: 10.1093/ofid/ofaa139
|View full text |Cite
|
Sign up to set email alerts
|

Ceftolozane/Tazobactam for Treatment of Severe ESBL-Producing Enterobacterales Infections: A Multicenter Nationwide Clinical Experience (CEFTABUSE II Study)

Abstract: Background Few data are reported in the literature about the outcome of patients with severe extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E) infections treated with ceftolozane/tazobactam (C/T), in empiric or definitive therapy. Methods A multicenter retrospective study was performed in Italy (June 2016–June 2019). Successful clinical outcome was defined as complete resolution of clinical signs/symptoms rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 26 publications
5
66
0
Order By: Relevance
“…The study highlighted the use of ceftolozane/tazobactam also in patients with ESBL-non-producing GNB infections. A careful analysis of the data has shown that this use coincided temporally with the lack of availability of piperacillin/tazobactam in Italy due to the high demand due to the increase in the incidence of ESBL-producing Enterobacterales [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study highlighted the use of ceftolozane/tazobactam also in patients with ESBL-non-producing GNB infections. A careful analysis of the data has shown that this use coincided temporally with the lack of availability of piperacillin/tazobactam in Italy due to the high demand due to the increase in the incidence of ESBL-producing Enterobacterales [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent meta-analysis showed no significant differences in the prognosis for BSIs caused by ESBL-E and treated with carbapenems or BL/BLIs, indicating the usefulness of BL/BLIs for empirical and definitive therapies [ 175 ]. A multicenter retrospective study performed in Italy between 2016 and 2019 revealed a high clinical success rate in patients who received ceftolozane-tazobactam in empiric and/or targeted therapy for severe infections [ 176 ]. Concerning new drugs for a carbapenem-sparing approach, a recent real-life study assessed the role of ceftazidime-avibactam for the targeted treatment of patients with ESBL-E infections in selected cases, but the small study sample limited the drawing of definitive conclusions [ 177 ].…”
Section: β-Lactamase-mediated Resistance In Enterobactermentioning
confidence: 99%
“…A recent Italian multicenter retrospective study reported the largest clinical experience regarding the use of C/T therapy for the treatment of serious ESBL-producing Enterobacteriales infections in daily clinical practice (NP 31.7%, acute bacterial skin and skin-structure infection [SSTI] 20.8%, cUTI 13.9%, cIAI 12.9%, bone infection 8.9% and primary bacteremia 5.9%), and showed C/T to be a valid option in empiric and/or targeted therapy, with favorable clinical outcomes in 128/153 (83.7%). Interestingly, the risk of clinical failure was associated with standard-dose C/T therapy in septic patients receiving continuous renal replacement therapy (CRRT) [ 26 ].…”
Section: Novel Treatment Optionsmentioning
confidence: 99%